Recalcitrant Lateral Premalleolar Bursitis of the Ankle Associated with Lateral Ankle Instability - Masashi Naito; Takumi Matsumoto; Song Ho Chang; Masachika Ikegami; Jun Hirose; Sakae Tanaka (Case Reports in Orthopedics)
Lateral premalleolar bursitis of the ankle is a rarely reported disorder in the English literature although it is not uncommon in Asian countries where people commonly sit on their feet. Here, we present the case of a 66-year-old woman with recalcitrant lateral premalleolar bursitis associated with lateral ankle instability which was successfully treated with surgical resection of the bursa and repair of the anterior talofibular ligament. Operative findings revealed a communication between the bursa and articular cavity of the ankle joint via the sheath of the extensor digitorum longus tendon, which was considered to act as a check valve leading to a large and recalcitrant bursitis. This report provides a novel concept about the etiology of recalcitrant lateral premalleolar bursitis of the ankle.